Studi Penelusuran Alumni Prodi Tadris/Pendidikan Matematika IAIN Padangsidimpuan - Deswinda Harahap; Suparni Suparni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The background of this research is the writer's curiosity to the Graduates of Mathematics department at IAIN Padangsidimpuan. This article will describe the competencies of graduates of Mathematics department after they work. This article will also describe whether the Mathematics department has been able to prepare graduates' competencies in facing the challenges of the job market. The results of this study indicate that 95% of graduates are already working. Most of the graduates work in the education sector as mathematics teachers at various levels of public and private schools. It can be said that the place where they work is in accordance with their skill background. However, many of them still receive a very low salaries. Many of Ther salaries are under one million. For them, it does not matter, the most important thing for them is they can work and they can apply their skills. Most of them are not too long to get the first job after graduated their studi, because before they graduate from their collage, they have started to look for a job.